Simulation of water supply control on water intakes facilities from underground sources - Purusova Irina; Chizhik Konstantin; Tolstoy Mikhail; Popova Ekaterina (BIO Web of Conferences)
Consideration is given to the enhancement of mathematical modeling of water supply regulation by subterranean water intake structures. The examination of publications using a mathematical model of how subterranean water intake structures function revealed that there hasn't been enough research done on how to solve problems when there is ambiguity and incompleteness of the initial data. A mathematical model of the functioning of the existing water intake facilities from Voronezh's underground sources was constructed using the actual characteristics of the interacting system parts. The distribution of water flows is described by a system of linear equations that include chain, nodal balance, and normal equations that create a balance between the inflow and flow of water at each node. A functional restriction is the balanced flow of water through the collecting duct and into the clean water tank. A control model using linear equations is proposed to forecast the submersible pump supply and to realistically assess the optimal joint functioning of the system comprising the well, submersible pump, collecting conduit, and clean water reservoir. An approach is proposed to solve a system of equations for controlling the water flow from wells to a clean water reservoir.